Peningkatan Keterampilan Menulis Surat Pribadi menggunakan Model Think Talk Write pada Siswa Kelas VII - Geovany, Uray; Thamimi, Muhammad; Hariyadi, Hariyadi (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This research has the general objective of describing the learning process and learning outcomes using the think talk write model for class VII students at Nurul Islam Middle School, Kubu Raya. In this research, there are two variables, namely the action variable and the outcome variable. The method used is descriptive method and the form of research is PTK. The subjects of this research were 40 students in class VII of Nurul Islam Middle School. The data analysis technique here uses critical analysis techniques and comparative descriptive techniques. The results of data analysis of the learning process went well based on teacher observations, increasing from the pre-cycle average score of 62.5, increasing in cycle I to 75, and increasing in cycle II to 82.81. Student observation results increased from the pre-cycle average score of 53.8, increased in the first cycle to 69.23, and increased in the second cycle to 82.69. The think talk write learning model can improve personal letter writing skills. Personal letter writing skills increased from an average score of 67.50 in pre-cycle, 68.55 in cycle I, and increased in cycle II to 78.72. The increase in grades has met the KKM, namely 70. Learning to write personal letters using the think talk write learning model for class VII students at Nurul Islam Middle School, Kubu Raya can be said to have increased.